Prediction of Postoperative Vocal Fold Function After Intraoperative Recovery of Loss of Signal. (24th September 2018) - Schneider, Rick; Randolph, Gregory; Dionigi, Gianlorenzo; Barczynski, Marcin; Chiang, Feng‐Yu; Wu, Che‐Wei; Musholt, Thomas; Uludag, Mehmet; Makay, Özer; Sezer, Atakan; Teksöz, Serkan; Weber, Theresia; et al.
Abstract : Objectives/Hypothesis: This multicenter study aimed to 1) evaluate early postoperative vocal fold function in relation to intraoperative amplitude recovery, and 2) determine optimal absolute and relative thresholds of intraoperative amplitude recovery heralding normal early postoperative vocal fold function, both after segmental type 1 and after global type 2 loss of signal (LOS). Study Design: Prospective outcome study. Methods: This study, encompassing nine surgical centers from four countries, correlated intraoperative amplitude recovery with early postoperative vocal fold function using receiver operating characteristic analysis. Results: Included in this study were 68 patients, 48 women and 20 men, who sustained transient recurrent laryngeal nerve injury during thyroid surgery under continuous intraoperative nerve monitoring. Early transient vocal fold palsy was seen in 18 (64%) of 28 patients with ipsilateral segmental LOS type 1, and in 10 (25%) of 40 patients with ipsilateral global LOS type 2. On receiver operating characteristic analysis, relative amplitude thresholds were superior to absolute amplitude thresholds in predicting vocal fold function after LOS type 2 (area under the curve [AUC]: 0.83 vs. 0.65; P = .01 vs. P = .15; Youden index 44% and 253 µV) and LOS type 1 (AUC: 0.96 vs. 0.97; P < .001 each; Youden index 49% and 455 µV). Amplitude recovery ≥50% of baseline after LOS always indicated intact vocal fold function. Conclusions: When the nerve amplitude recovers ≥50% of baseline after segmental LOS type 1 or global LOS type 2, it is appropriate to extend completion thyroidectomy to the other side during the same session. Level of Evidence: 2b Laryngoscope, 129:525–531, 2019